Adaptation of the Barts Explanatory Model Inventory to dementia understanding in South Asian ethnic minorities. (2nd June 2016) - Giebel, Clarissa M.; Jolley, David; Zubair, Maria; Bhui, Kamaldeep Singh; Challis, David; Purandare, Nitin; Worden, Angela
Abstract : Objective: Studies indicate a limited understanding of dementia and its associated symptoms, causes and consequences among South Asian older adults. As a consequence, fewer people from this ethnic group receive a diagnosis of dementia. The aim of this study was to adapt the previously designed Barts Explanatory Model Inventory Checklist (BEMI-C), a tool designed to elicit perceptions of mental illness from people with different cultural backgrounds, for use with people with dementia in the South Asian population. Method: Both a literature review and 25 qualitative interviews were conducted to find themes and perceptions that are relevant to the South Asian culture in recognising and dealing with symptoms of dementia. The emergent themes and perceptions were then added to the BEMI-C through synthesis of findings. Results: The initial four checklists of symptoms, causes, consequences and treatments from the BEMI-C were retained in the new BEMI-Dementia (BEMI-D) and expanded with six additional themes, including 123 new perceptions relevant to the understanding of dementia. All new themes emerged from the qualitative interviews, some of which were also found in the literature. Conclusion: Given the national priority of improving dementia awareness and timely diagnosis, the BEMI-D can serve as a useful tool, in research and perhaps practice, to assess the barriers to dementia service uptake in this population and their understandings of dementia. Based on the detailed methodological description of the adaptation of the BEMI-C, this paper further suggests how this tool can be adapted to suit other ethnic minority groups.